2019
DOI: 10.3390/md17080484
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Lipid Production and Molecular Dynamics under Salinity Stress in Green Microalga Chlamydomonas reinhardtii (137C)

Abstract: Microalgal lipids are a source of valuable nutritional ingredients in biotechnological industries, and are precursors to biodiesel production. Here, the effects of salt-induced stresses, including NaCl, KCl, and LiCl stresses, on the production of lipid in green microalga Chlamydomonas reinhardtii (137c) were investigated. NaCl stress dramatically increased saturated fatty acids (SFAs), which accounted for 70.2% of the fatty acid methyl ester (FAMEs) under stress. In contrary, KCl stress led to a slight increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 35 publications
(36 reference statements)
3
20
0
1
Order By: Relevance
“…Due to the diverse phylogeny of microalgae, significant differences do occur in the types of fatty acids partitioned into TAG upon reception of salinity stress. For example, it was observed that Chlorophyta tended to synthesises saturated fatty acids (SFA) and monounsaturated fatty acids (MUFA) while Ochrophyta (diatoms) preferred production of polyunsaturated fatty acids (PUFA) when stressed 5 . However, regardless of phylogeny, oleaginous microalgae will rearrange its lipid pathways in order to accumulate high amounts of TAG (about 40–70% per dry weight) upon exposure to abiotic stress conditions 4 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the diverse phylogeny of microalgae, significant differences do occur in the types of fatty acids partitioned into TAG upon reception of salinity stress. For example, it was observed that Chlorophyta tended to synthesises saturated fatty acids (SFA) and monounsaturated fatty acids (MUFA) while Ochrophyta (diatoms) preferred production of polyunsaturated fatty acids (PUFA) when stressed 5 . However, regardless of phylogeny, oleaginous microalgae will rearrange its lipid pathways in order to accumulate high amounts of TAG (about 40–70% per dry weight) upon exposure to abiotic stress conditions 4 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Increased accumulation of saturated fatty acids might protect the membrane fluidity to protect the cell and cellular organelle from Na + toxicity and ion leakage (Shu et al, 2015;Atikij et al, 2019). Our results also showed an increase in coumarate and benzoate in both leaves and roots, while significant increase was observed in caffieate and ferulate levels only in roots of salt treated plants.…”
Section: Discussionsupporting
confidence: 61%
“…In freshwater microalgae, changes in 16:0 and 18:0 with salt concentration are also variable. In C. reinhardtii, high salt conditions resulted in 16:0 depletion and 18:0 enrichment, 141 but also in enrichment 99,128 and minor changes in both FA. 174 16:0 and 18:0 changed little in Chlamydomonas mexicana over the 0-100 mM NaCl range, 175 and sea ice Chlamydomonas sp.…”
Section: Pros Pec Tingtherel Ati On S Hip B E T Weensatur Atedfat T Yacidsand Salinit Yinmi Croalg Aementioning
confidence: 95%
“…Most of this genomic information is based on genome predictions of orthologous genes in seed plants and is pending experimental verification. 127 Under increased NaCl concentration, TG biosynthesis genes were downregulated in N. oleabundus, 73 Chlamydomonas reinhardtii 128 and P. kessleri. 75 In C. zofingiensis, only one in ten diacylglycerol acyltransferase (DGAT) genes was upregulated by salt stress.…”
Section: Con S Ider Ati On Sonthe Rel Ati On S Hipb E T Weensalinit Yand Tri G Lyceridecontentmentioning
confidence: 99%
See 1 more Smart Citation